The SOS File - Byars, Betsy Cromer; Duffey, Betsy; Myers, Laurie; Howard, Arthur (New York : Henry Holt, 2004)
The students in Mr. Magro's class submit stories for the SOS file about their biggest emergencies, and then they read them aloud for extra credit.
Keywords: Storytelling -- Fiction; Schools -- Fiction